Speech Rhythm in Spontaneous and Controlled L2 Speaking Modes: Exploring Differences and Distance Measures - Katherine Fraser; Joan C. Mora (Research in Language)
Studies of speech rhythm have often used read speech rather than spontaneous speech in their comparisons. However, read speech has been shown to be perceptually different from spontaneous speech, which may be due to rhythmic differences between the two modes. To examine this, the effect of speaking mode (spontaneous or controlled) was assessed in a group of 82 Spanish-Catalan learners of English relative to a control group of 8 native English speakers. Results found strong rhythmic differences between the two modes, but minimal differences between the learners and native speakers. Additionally, Mahalanobis distance analyses revealed that non-native speakers differed significantly more from the native control group in the spontaneous condition than the controlled condition.